Impact of CYP1A2 genetic polymorphisms on pharmacokinetics of antipsychotic drugs: a systematic review and meta-analysis - M. Na Takuathung (2018)
© 2018 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Objective: To determine the impact of CYP1A2 genetic polymorphisms on the pharmacokinetics of CYP1A2-metabolized antipsychotic drugs in humans by means of systematic review and meta-analysis. Method: A systematic search was conducted in PubMed and Scopus databases as of June 26, 2018. Studies reporting the pharmacokinetic parameters of CYP1A2-metabolized antipsychotic drugs in individuals who were genotyped for CYP1A2 genetic polymorphisms were retrieved. Pharmacokinetic parameters of individuals who have mutant alleles of a CYP1A2 genetic polymorphism were compared with the wild-type individuals. Pooled-effect estimates, presented as standardized mean difference, were calculated by means of the fixed-effect or random-effects model, as appropriate. Results: Ten studies involving 872 clozapine users, seven studies involving 712 olanzapine users, and two studies involving 141 haloperidol users were included. All but one study reported no associations between any CYP1A2 genetic polymorphisms and the pharmacokinetics of CYP1A2-metabolized antipsychotic drugs. The pooled-effect estimates through meta-analyses of seven studies demonstrated no significant associations between the -163C>A or -2467delT polymorphism and clozapine or olanzapine concentrations in the blood. Conclusions: This study suggests that CYP1A2 genetic polymorphisms have no significant impact on the pharmacokinetics of CYP1A2-metabolized antipsychotic drugs. CYP1A2 genotyping may have no clinical implications for personalized dosing of CYP1A2-metabolized antipsychotic drugs.